The Impact of Using DME as a Substitute for LPG in Indonesian Economy - Setiya, Banu; Hartono, Djoni (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractIn order to reduce the import ratio and high budget needs for energy subsidies, the government of Indonesia is currently developing DME production to replace LPG as fuel in cooking activities. From various previous studies, the policy of using DME not only requires a relatively expensive cost but also has the potential to disrupt health and endanger environmental sustainability due to the use of large amounts of fossil energy from coal. This study aims to examine the impacts of DME policy on the Indonesian economy using the CGE method, 2019 SAM data and two forms of shocks: (i) Decreasing LPG imports and (ii) Reallocating the subsidies budget. DME will have a positive impact on the economy, trigger growth in the productivity of various sectors and encourage employment, but only in the short run. The results of the study in the long run show negative implications even though the percentages are relatively low and not significant. Keywords: CGE, DME, Energy Subsidies, Import, LPG